The Growth Response of Kale Land (Ipomoea reptans Poir) to the Aplications of Vermicompost and NPK Fertilizer - Ahmad Raksun; Mohammad Liwa Ilhamdi; I Wayan Merta; I Gde Mertha (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Kale land is a short-lived plant, containing the nutrients needed by the human body. The growth of kale land is influenced by various factors, one of which is the adequate supply of nutrients needed by plants. Fertilization is one of the efforts that can be done to ensure the availability of nutrients on agricultural land. Research has been carried out on the growth response of kale land due to the application of vermicompost and NPK fertilizers. The purpose of this research is to obtain information about (1) increased growth of kale land due to the application of vermicompost, (2) increased growth of kale land due to application of NPK fertilizer, (3) increased growth of kale land due to the interaction of vermicompost and NPK fertilizer treatments. The research was carried out using an experimental method in the form of factorial arranged according to a completely randomized design. The first factor is vermicompost (C) with doses of 0 kg, 0.4 kg, 0.8 kg, 1.2 kg and 1.6 kg vermicompost per square meter of agricultural land. The second factor is the application of NPK fertilizer (P) at a dose of 0 g, 0.5 g, 1 g, 1.5 g per plant. Thus there were 20 treatment combinations and each combination was carried out with 3 replications. The growth parameters observed were plant height, total leaf, leaf length, leaf width and stem diameter of land kale. Research data were analyzed by Anova. The conclusions of the study were: (1) The application of vermicompost could increase plant height, number of leaves, leaf length and leaf width but could not increase stem diameter of kale land (2) application of NPK fertilizer can improve all growth parameters of kale land kangkong. (3) The interaction of vermicompost and NPK fertilizer cannot increase the growth of kale land.